Associação entre a expressão das proteínas p53 e Ki-67 e os achados clínico-patológicos em pacientes com carcinoma invasor do colo uterino - Silva-filho, Agnaldo L. [UNESP]; Bruno, Bernardo Nascentes; Silva, Lucas Barbosa Da; Traiman, Paulo [UNESP]; Castro E Silva, João Gilberto De; Triginelli, Sérgio Augusto (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2005)
PURPOSE: to evaluate the association between p53 and Ki-67 expression in the tumor and clinicopathological features in patients with carcinoma of the cervix. METHODS: samples were taken from the tumor of 36 patients with stage IB (FIGO) cervical carcinoma submitted to radical hysterectomy. Tissue samples were taken from the tumor, fixed in formalin and embedded in paraffin. The specimens were analyzed by histopathology (hematoxylin and eosin) and immunohistochemically evaluated using monoclonal antibodies for p53 and Ki-67. Data were analyzed statistically by the chi2 test to evaluate eventual differences between the groups. RESULTS: the age of the patients ranged from 27 to 73 years (48.7±10.4 years). Clinical stage (FIGO) was IB1 in 27 cases (75%) and IB2 in 9 cases (25%). A positive tumoral expression of the p53 protein was found in half of the cases. In relation to the Ki-67 expression, a high cell proliferation index was shown in 73.3% of the cases. There was no association between tumoral p53 and Ki-67 expression with age (p=0.091 and 0.900), clinical stage (p=0.054 and 0.667), histological classification (p=0.674 and 0.674), grade of differentiation (p=0.070 and 0.282), presence of lymphatic vascular space invasion (p=0.248 and 0.667), parametrial involvement (p=0.729 and 0.763) and pelvic lymph node metastasis (p=0.729 and 0.636, respectively). CONCLUSIONS: tumoral expression of p53 and Ki-67 was not associated with the clinicopathological features in patients with stage IB carcinoma of the cervix.

OBJETIVO: avaliar a associação da expressão das proteínas p53 e Ki-67 no tumor com achados clínico-patológicos em pacientes com carcinoma invasor de colo uterino. MÉTODOS: foram estudadas amostras de tumor obtidas de 36 pacientes submetidas a histerectomia radical para tratamento de carcinoma invasor do colo uterino estádio IB (FIGO). Amostras do tumor foram fixadas em formol e incluídas em parafina. O material foi analisado pela histopatologia (hematoxilina e eosina) e processado para marcação imuno-histoquímica por anticorpos monoclonais contra as proteínas p53 e Ki-67. Os dados foram analisados pelo teste de chi2 para a avaliação das diferenças entre os grupos. RESULTADOS: a idade das pacientes variou de 27 a 73 anos (48,7±10,4 anos). O estadiamento clínico (FIGO) foi IB1 em 27 casos (75%) e IB2 em 9 casos (25%). A expressão tumoral da proteína p53 foi positiva em metade dos casos. Em relação à expressão do Ki-67, foi evidenciado alto grau de proliferação celular em 73,3% dos casos. Não houve associação da expressão das proteínas p53 e Ki-67 no tumor com idade (p=0,091 e 0,900), estadiamento (p=0,054 e 0,667), tipo histológico (p=0,674 e 0,674), grau de diferenciação (p=0,07 e 0,282), presença de invasão linfovascular (p=0,248 e 0,667), acometimento parametrial (p=0,729 e 0,763) e metástases para os linfonodos pélvicos (p=0,729 e 0,636, respectivamente). CONCLUSÕES: a expressão tumoral das proteínas p53 e Ki-67 não se associou com achados clínico-patológicos em pacientes com carcinoma invasor do colo uterino estádio IB.
Association between p53 and Ki-67 expression and clinicopathologic features in patients with carcinoma of the cervix
Keywords: Cervix neoplasms; Oncogenes; Protein p53; Ki-67 antigen; Neoplasias do colo uterino; Oncogenes; Proteina p53; Antígeno Ki-67